Adjusting N, K, Mg and Cu Rates for Improvement of Fertilizer N Use Efficiency in Rice Production in Malaysia - Mohamad Ali Choudhury, Abu Turab (1999)
The largest rice growing area of Malaysia is located in the Muda Irrigation Scheme. Recent investigations showed that N use efficiency by rice crop is very low in many locations of this Irrigation Scheme due to Cu and Mg deficiency. It is important to increase N use efficiency in rice culture in order to increase yield through better fertilizer management. Three laboratory, three greenhouse and one field experiments were carried out to determine the possible mechanisms for improvement of fertilizer N use efficiency in rice production. Potassium, Mg and Cu status of different rice soils were determined. Deficiencies of K, Mg and Cu were found in 5, 4 and 7 soils, respectively. Three laboratory experiments were carried out on adsorption of K, Mg and Cu in different rice soils. The data indicated that adsorption of K, Mg and Cu depends on soil pH. The first greenhouse experiment was conducted to evaluate the effects of N and Cu fertilization on rice yield and fertilizer N use efficiency in rice culture. Nitrogen was applied as 1 5N labelled urea. Estimated grain yield response to added N was quadratic in nature. Copper effect was not significant on grain yield. Effects of N and Cu were not significant on recovery (%) of fertilizer N. The second greenhouse experiment was conducted to evaluate the effects of N and Mg fertil ization on rice yield and fertilizer N use efficiency in rice culture. Nitrogen was applied as 1 5N labelled urea. Grain yield increased significantly due to N and Mg application. Fertilizer N uptake and recovery increased significantly with increasing Mg rates. These findings suggest that there is a prospect to increase grain yield and fertilizer N use efficiency by Mg application in Mg deficient soils. The third greenhouse experiment was conducted to evaluate the effects of K and Mg fertilization on yield, and K and Mg uptake by rice. Grain yield, K and Mg uptake increased significantly due to Mg fertilization whereas the effect of K was not significant. The field experiment was conducted to evaluate the effects Cu and Mg application on grain yield and agronomic efficiency of added N. Grain yield and agronomic efficiency of added N increased significantly due to Cu or Mg application. These findings suggest that combined application of Cu and Mg both at 10 kg ha-1 along with 120 kg N ha-1 can increase grain yield of rice by 24% in soils deficient in both Cu and Mg.